المنازعات الجبائية بين الوعاء والتحصيل في التشريع الجزائري - دليلة, عيشوش; عريق, مباركة; خليفة, سهام (University of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة إلى تسليط الضوء على موضوع المنازعات الضريبية التي تكتسي أهمية بالغة، حيث تظهر الأهمية النظرية من خلال النصوص القانونية التي أقرها المشرع الجزائري في مختلف القوانين والنصوص التنظيمية التي تحكم هذا النوع من النزاعات، ومن حيث تطبيق النصوص والإجراءات القانونية المعتمدة من قبله. المشرع عند نشوء النزاع الضريبي ومدى فاعليته في تسويته إداريا وقضائيا. يكمن الدور الرئيسي للنزاعات الضريبية في إعادة . Abstract: This study aims to shed light on the issue of tax disputes, which are very important, as the theoretical importance appears through the legal texts approved by the Algerian legislator in the various laws and regulatory texts that govern this type of disputes, and in terms of applying the legal texts and procedures approved by him. The legislator when the tax dispute arises and the extent of its effectiveness in settling it administratively and judicially. The main role of tax disputes lies in resolving the dispute or conflict. It is the settlement of the complaint at the level of the tax administration and the adjudication of the case at the level of the judiciary, so that there are two types of disputes, some of which are related to the base and others are related to recovery.
مذكرة ماستر
Keywords: المنازعات الجبائية، الإدارة الجبائية، الوعاء، التحصيل; Tax disputes, tax administration, container, recovery